PENGEMBANGAN MEDIA PEMBELAJARAN MABAJEMA: MARI BELAJAR JENIS MAJAS BERBASIS MODEL CIRC UPAYA PENINGKATAN PEMAHAMAN MATERI MAJAS PADA SISWA KELAS V SD NEGERI TAMBANGAN 02 KOTA SEMARANG - Musyaffa, Irsyad Fadhil; Ida Zulaeha; Panca Dewi Purwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research focuses on the development of MABAJEMA learning media: Let's Learn Types of Majas for Indonesian language subjects. Majas is a word made by the author to emphasize and beautify a word/sentence. Majas itself is divided into several types, one of which is metaphor, personification, and hyperbole. Majas material in Indonesian is abstract and difficult for students to understand because it cannot be seen directly. In addition, educators only use the lecture approach and the lack of learning media makes learning Indonesian less effective. This type of research is development research (R&D) using the ADDIE model, and includes analysis, design, development, implementation, and evaluation. The developed media was then validated by material and media experts. The results of media feasibility showed a value of 93.33% and material feasibility of 95%. This shows that the media is very feasible to develop. In addition, the results of the T-test and N-gain pre-test and post-test showed a sig. (2-tailed) of 0.0001 in the T-test and 56.33% in the N-gain test, indicating that the learning media developed is quite effective and can help students improve students' understanding of Indonesian language majas material.